The National Spina Bifida Patient Registry: A Decade's journey. Issue 14 (6th November 2018) - Castillo, Jonathan; Lupo, Philip J.; Tu, Duong D.; Agopian, A.J.; Castillo, Heidi
Abstract : Background: The National Spina Bifida Patient Registry (NSBPR) was established in 2008, as a partnership between the CDC and spina bifida (SB) clinics throughout the United States. The purpose of this study is to explore the initial work of this project through a literature review of published studies from the NSBPR and provide a description of how this body of literature has developed overtime. Methods: We included studies indexed in MEDLINE by means of PubMed from January 2009 through April 2018. Included articles were appraised to identify key themes relevant to SB demographics, interventions, and outcomes. Additionally, information regarding objectives, hypotheses, and results of each study was summarized. Results: We identified 13 articles meeting inclusion criteria. These publications described findings or explored associations using NSBPR variables. They were grouped into four categories: general characteristics (4 studies), mobility and skin injury (2 studies), bowel continence (3 studies), and bladder continence (5 studies). Conclusions: The NSBPR represents one of the largest described clinical samples of individuals living with SB. The first decade of studies have focused primarily on descriptive analyses and on identifying predictors of clinical outcomes. These initial results may help develop interventions (including culturally appropriate initiatives), be a resource for developing international evidence‐based standards of care and best‐practices, and lead to improved outcomes for individuals living with SB globally. Additionally, the results underscore the strengths of the NSBPR's design and highlight the potential breadth of research topics that could be addressed in the future.